2016
DOI: 10.3390/jdb4030027
|View full text |Cite
|
Sign up to set email alerts
|

Control of Hedgehog Signalling by the Cilia-Regulated Proteasome

Abstract: The Hedgehog signalling pathway is evolutionarily highly conserved and essential for embryonic development of invertebrates and vertebrates. Consequently, impaired Hedgehog signalling results in very severe human diseases, ranging from holoprosencephaly to Pallister-Hall syndrome. Due to this great importance for human health, the focus of numerous research groups is placed on the investigation of the detailed mechanisms underlying Hedgehog signalling. Today, it is known that tiny cell protrusions, known as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 131 publications
1
19
0
Order By: Relevance
“…Hedgehog (HH) signaling is also a major pathway regulated by both the primary cilium and the proteasome (40). We therefore asked whether disruption of USP35 affects HH signaling transduction.…”
Section: Resultsmentioning
confidence: 99%
“…Hedgehog (HH) signaling is also a major pathway regulated by both the primary cilium and the proteasome (40). We therefore asked whether disruption of USP35 affects HH signaling transduction.…”
Section: Resultsmentioning
confidence: 99%
“…So far, it is unknown whether the degradation systems participate in the TZ assembling or whether other TZ proteins than Rpgrip1l govern proteasomal and/or autophagic activity. Most likely, the cilia‐regulated proteasome is involved in the regulation of numerous cilia‐mediated signalling pathways (Gerhardt et al , ,b) but, as discussed by us and others before, proteasomal dysfunction is probably not the main reason for the development of ciliopathies (Liu et al , ; Gerhardt et al , ). To reveal the molecular processes underlying ciliopathies caused by mutations in RPGRIP1L , future studies should clarify to what extent the disturbances in TZ assembling and of the degradation systems contribute to the ciliopathy of Rpgrip1l −/− mouse embryos, whether proteasomal activity at the ciliary base and/or autophagic activity are affected in patients suffering from ciliopathies caused by mutations in RPGRIP1L and if there are interactions between TZ assembling and the degradation systems which ensure the proper development and homeostasis in vertebrates.…”
Section: Discussionmentioning
confidence: 97%
“…[160] Additional mutations, such as loss-of-function mutations in SUFU, increase the nuclear transport of GLI2 and enhance hedgehog signaling, resulting in the aggressive growth of medulloblastoma and BCC resistant to SMO inhibitors. [174][175][176] β-Transducin repeat-containing E3 ubiquitin protein ligase (β-TRCP) is an F-box protein associated with an adaptor protein, SKP1, a scaffold protein, Cul1, and RING protein Rbx1, which together act as an E3 ligase complex. [160,161] Small molecules have been identified that inhibit GLI-A [162,[165][166][167][168][169][170][171] and reintroduce primary cilia.…”
Section: Hedgehog Signaling Regulates Cancer Cell Proliferation Throumentioning
confidence: 99%